Ringgit Emas Sekarang (RES) / Tuan Badrol HishamTuan Besar, Sharidatul Akma Abu Seman and Ahmad Rais Mohamad Mokhtar - Tuan Besar, Tuan Badrol Hisham; Abu Seman, Sharidatul Akma; Mohamad Mokhtar, Ahmad Rais (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Ringgit Emas Sekarang (RES) is an application that will provide information to user on what is the current RINGGIT for GOLD. The price is on time (real time) basis and can be used as a tool for the user in their decision in buying or selling the GOLD in the market. It is an improvement form batching-price and USD price toward real-time price application. RES can be used as a tool in making decision such as buying or selling the GOLD in the market. RES has a commercial potential towards GOLDier, such as a retail user, retail trader, broker and also investor may benefit from the RES.